Perfil clínico-radiológico das crianças hospitalizadas por pneumonia causada pelo Mycoplasma pneumoniae - Leticia Alves Vervloet (2007)
The objective of this study was to describe the radiological profile of hospitalized children with Mycoplasma pneumonia, to compare with pneumonia caused by other etilogic agents and to evaluate the accuracy of a clinical, laboratorial and radiographic score in differenciate Mycoplasma pneumonia from pneumonia caused by other bacterias or non-bacterias (viruses and other agents). This study covered 190 pacients aged 3 month to 16 years hospitalized in the Pneumology Service of Nossa Senhora da Glória Childrens Hospital (HINSG), Vitória, Espírito Santo, Brazil, between January 2000 and December 2005, who were distributed in two groups diagnosed by enzyme immunoassays (ELISA): (1) 95 children with Mycoplasma pneumonia; (2) 95 children with other agents' pneumonia. Afterwards a score was used to differenciate Mycoplasma pneumonias (first group) from pneumonias caused by other etilogical agents (second group) divided in bacterial pneumonias (n=75) and non-bacterial pneumonias (n=20). Mycoplasma pneumonia predominated in female children (p=0,0023), elderly aged (p=0,0001), with nonproductive cough (p=0,0001) and extrapulmonary manifestations (p=0,0000). If wheezinhg was observed, mycoplasma pneumonia demanded enhacement of intravenous salbutamol (p=0,0008). Using the score developed by Moreno et al, the clinical, laboratorial and radiographic variations of Mycoplasma pneumonia had, in most cases, intermedial pontuations between bacterial pneumonia and non-bacterial pneumonia (viruses and other). The results show that some clinical and radiographic signs may contribute to differentiate Mycoplasma pneumonia from those pneumonias causes by other etiological agents.